Analisis Penggunaan E-Wallet Terhadap Mahasiswa Universitas Islam Sumatera Utara Tahun 2022 - Farhan, M; Sadly, Effendi; Neruz, Milla (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2023)
The background of this thesis research is that the development of the digitalization era is getting faster and faster, demanding changes in the transaction sector using digital applications (E-Wallets) that are increasingly modern and efficient. The times have given rise to various payment methods through digital applications such as OVO and DANA.The use of e-wallets in big cities in Indonesia is increasing every year. Most users of e-wallets are millennials, especially students. This study examines the use of e-wallets among students, especially at the Islamic University of North Sumatra, such as how students know about e-wallets, the impact of using e-wallets, and problems using e-wallets in transactions. This research method uses a quantitative research type. The data source used is primary data obtained from questionnaires distributed to respondents, namely students of the Islamic University of North Sumatra, as many as 100 respondents. The sampling technique used in this study is the stratified random sampling technique. Questionnaire data were analyzed using SPSS 25.0 by carrying out several stages of data analysis test, validity test, reliability test, classical assumption test, multiple linear regression test, hypothesis test (t and F test) and the coefficient of determination (R2). Based on the results of the study with the partial test (t), there is a positive and significant effect in the OVO and DANA (X1) E-Wallet application on students as evidenced by the value obtained by t-count t-table, namely 2.124 1.984 and a significance value of 0.308 0.05, then H0 is rejected and H1 is accepted, and there is no positive and significant effect on the impact of using E-Wallet (X2) and problems using E-Wallet on students (Y ) as evidenced by the financial literacy value (X2) obtained by t-count t-table, namely 2.475 1.984 and a significance value of 0.720 0.05 then H0 is rejected and H1 is accepted. While using the simultaneous test (F) it is known that the F-count value is 0.391 F- table of 1.984 and Prob α = 0.760 0.05 so that it can be said simultaneously that variables X1 (OVO E-Wallet and DANA), X2 (Effects of using E-Wallet), and X3 (Problems using E-Wallet) have a significant and significant effect on Y (UISU Student). The coefficient of determination R2 shows 0.112 with a percentage of 11.2%.